2021
DOI: 10.20473/fmi.v55i1.24386
|View full text |Cite
|
Sign up to set email alerts
|

Lactate Level as a Prediction Factor of Reperforation after Repairing Gastric Perforation

Abstract: Reperforation after gastric perforation repair is a complication which increases the rate of morbidity and mortality in gastric perforation. The lack of ability of the tissue to use oxygen in septic condition causes anaerobic cellular metabolism and furthermore it will cause failure in closing the perforation. The production of anaerobic metabolism is lactic acid which can be measured from the blood. The aim of this study is to determine the cut-off point of blood lactate level as a predictor of reperforation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Fecal induced peritonitis for animal research as identical as human model data which caused sepsis based on SOFA Score evaluation, inflammatory response duration from induction until host bacteremia condition is consistent although sepsis duration is not (Park I, et al, 2019). In septic condition there is a defect in cellular oxygen utilization, anaerobic metabolism occur and blood lactate level will increase as a result (Budipramana VS, 2021). An initial supportive therapy and parenteral broadspectrum antibiotics were prominently important to undertake while waiting for further diagnostics and therapies arrangements were made (Pranata AK, 2021).…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…Fecal induced peritonitis for animal research as identical as human model data which caused sepsis based on SOFA Score evaluation, inflammatory response duration from induction until host bacteremia condition is consistent although sepsis duration is not (Park I, et al, 2019). In septic condition there is a defect in cellular oxygen utilization, anaerobic metabolism occur and blood lactate level will increase as a result (Budipramana VS, 2021). An initial supportive therapy and parenteral broadspectrum antibiotics were prominently important to undertake while waiting for further diagnostics and therapies arrangements were made (Pranata AK, 2021).…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…[5][6][7][8][9] Early systemic infection and systemic inflammation could be identified by various laboratory parameters, such as leucocyte, lactate level, and C-reactive protein. 10,11 Currently, there are various sepsis severity score systems available, and they are useful for predicting mortality in cIAI patients. The SOFA (Sequential Organ Failure Assessment) score could be used generally in cases of sepsis, while the CPIRO (Calgary Predisposition Infection Response and Organ Dysfunction) scores and the WSESSSS (World Society of Emergency Surgery Sepsis Severity Score) were thought to be accurate in a large population with cIAI.…”
Section: Introductionmentioning
confidence: 99%
“…This score is widely used because it is easy in daily practice because it only assesses 3 variables components; namely the onset of perforation, shock at first admission, and comorbid disease; which is easy to do and has pretty good accuracy. 1,8,9 A preliminary study by Boey et al showed that patients with risk factors 0, 1, 2 and 3 who underwent laparotomy had a mortality rate of 0%, 14.1%, 58% and 100%. 2 The results of Boey's research (1982) are almost the same as the results of research conducted at the Dr. Soetomo Hospital in Surabaya, it was found that from a total of 33 cases of gastric perforation performed by laparotomy in 2018, 27.3% of cases of gastric perforation were obtained with a Boey score 2 assessment with a mortality rate of 11.1.…”
Section: Introductionmentioning
confidence: 99%